Politics in Nigerian Education; Freedom and Democratic Participations - Iorwuese, Afatyo (Kashere Journal of Education, 2025)
This paper discussed freedom in the Nigerian educational system. Freedom in the Nigerian educational system remains a central determinant of quality, inclusiveness and democratic participation, especially when reforms and societal changes continue to reshape schools. This paper explores the meaning and dimensions of freedom in education, emphasising academic, administrative, intellectual, professional, religious and cultural liberties. It examines how freedom manifests across students, teachers, administrators, parents and communities, highlighting rights to expression, professional autonomy, institutional decision-making and stakeholder participation. The legal and policy foundations supporting educational freedom, such as constitutional guarantees, the National Policy on Education and human rights instruments, are reviewed to assess their effectiveness in practice. The study also outlines the benefits of freedom, including improved creativity, teacher motivation, institutional accountability and enhanced learning outcomes. However, significant challenges persist, including political interference, centralised curriculum control, underfunding, insecurity, cultural pressures and restricted student activism. Current realities in 2025, including digital academic freedom, policy reforms and regional disparities, reveal both progress and gaps. The paper proposed strategies for strengthening educational freedom through improved legislation, decentralisation, adequate funding, enhanced safety and democratic school governance. The paper concluded that Freedom in the Nigerian educational system remains both a fundamental right and a condition for high-quality schooling. Ultimately, expanding educational freedom will shape a more innovative, accountable and equitable future for Nigerian learners. It was recommended, among others, that the government should strengthen legal frameworks to limit political control over school administration by enforcing merit-based appointments and transparent oversight. This should be done through independent monitoring bodies. The expected result increased institutional autonomy and improved quality of educational decisions